2009
DOI: 10.1136/bmj.b2968
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cervical screening with age: population based case-control study of prospectively recorded data

Abstract: Objective To study the effect of cervical screening on incidence of cervical cancer as a function of age with particular focus on women screened under the age of 25. Design Population based case-control study with prospectively recorded data on cervical screening. Setting Selected centres in the United Kingdom. Participants 4012 women aged 20-69 with invasive cancer diagnosed in participating centres and two controls per case individually matched on age and area of residence. Main outcome measures Odds ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
254
0
19

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(290 citation statements)
references
References 21 publications
17
254
0
19
Order By: Relevance
“…2,3,11 This study indicates that also when using mortality as outcome, screening in younger ages (below 40) has less impact than in older women. Because of a small number of deaths among invited women, it was not possible to estimate ORs for the associations of screening participation in the individual 5-year age categories.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…2,3,11 This study indicates that also when using mortality as outcome, screening in younger ages (below 40) has less impact than in older women. Because of a small number of deaths among invited women, it was not possible to estimate ORs for the associations of screening participation in the individual 5-year age categories.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, a case-control study from the UK found screening to be less effective in women aged 20-34 and that the efficacy decreases with decreasing age even within this age range. 3 By contrast, a Swedish audit found screening to be equally effective in preventing cancer diagnosed in the ages 21-29 and 30-65. 4 To our knowledge no mortality based effectiveness studies have yet addressed this issue.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Recent evidence supports the conclusion that cervical screening in women aged 20-24 is substantially less effective in preventing cancer than screening in older women (Sasieni et al 2009), not least because changes in the young cervix are normal, and unnecessary treatment in response to putative abnormal features could interfere with fertility (Arbyn et al 2008). Nonetheless, the decision to begin routine screening at 25 rather than 20 has been much debated, and in May 2009 an ‗extraordinary meeting' of the Advisory Committee on Cervical Screening (ACCS) was asked to make recommendations to government ministers about whether the age 25 start date was still the right policy.…”
Section: Introductionmentioning
confidence: 88%
“…Sasieni et al 22 mostraram que o rastreamento em mulheres com idade entre 20 e 24 anos teve pequeno ou nenhum impacto sobre as taxas de câncer cervical invasivo. Em contraste, o rastreamento em mulheres idosas obteve uma substancial redução na incidência e mortalidade em decorrência do CCU.…”
Section: Tabelaunclassified